MicroRNA-642b-3p functions as an oncomiR in gastric cancer by down-regulating the CUB and sushi multiple domains protein 1/smad axis. Issue 4 (1st April 2022) - Liu, Haofeng; Chen, Yuan; Zhou, Linsen; Jiang, Xiaohui; Zhou, Xiaojun
ABSTRACT: Aberrant expression of microRNAs (miRNAs or miRs) has been involved in the progression of gastric cancer (GC). Our analysis of GC-related gene expression profiles identified the significantly up-regulated miR-642b-3p expression, which has been reported as a mediator in various cancers but rarely mentioned in researches on GC. Herein, this study intends to investigate the role of miR-642b-3p in GC development. Bioinformatics analysis was conducted to predict the downstream target gene of miR-642b-3p. Expression patterns of miR-642b-3p and CUB and sushi multiple domains protein 1 (CSMD1) in GC tissues and cell lines was then determined. Immunofluorescence, wound healing and Transwell invasion assays were performed to observe the malignant behaviors of GC cells with altered expression of miR-642b-3p and CSMD1. Nude mice with xenograft tumors were developed for in vivo validation. miR-642b-3p expression was increased in GC tissues and cell lines. miR-642b-3p targeted CSMD1 and reduced the expression of CSMD1, thereby inhibiting the activation of Smad signaling pathway. By this mechanism, the epithelial–mesenchymal transition (EMT), invasive and migratory potentials of GC cells were repressed. Meanwhile, in vivo data verified that miR-642b-3p enhanced the tumor growth of GC cells, which was associated with blockade of CSMD1-dependent activation of the Smad signaling pathway. Overall, miR-642b-3p acts as an oncomiR promoting tumor development in GC through suppressing CSMD1 expression and inactivating the Smad signaling pathway, which may enable the development of new therapeutic strategies for treatment of GC. Graphical abstract: uf0001